Early rapid weight gain among formula‐fed infants: Impact of formula type and maternal feeding styles. Issue 6 (10th January 2019) - Mennella, J. A.; Papas, M. A.; Reiter, A. R.; Stallings, V. A.; Trabulsi, J. C.
Summary: Background: What and how infants are fed are considered important determinants for the risk factor of early rapid gain weight. Objectives: We conducted secondary analyses on data from a randomized clinical trial, wherein infants randomized to feed cow milk formula had double the incidence of early rapid weight gain than those fed extensively hydrolyzed protein formula, to determine whether maternal feeding styles had independent effects or interactive effects with infant formula type on early rapid weight gain. Methods: Anthropometry and feeding patterning (number of daily formula feeds) were measured monthly, and maternal feeding styles were measured at 0.5, 3.5, and 4.5 months. Longitudinal models were fitted using generalized estimating equations and separate logistic models conducted. Results: The treatment groups did not differ in formula feeding patterning or in maternal feeding styles, which were stable across the first 4.5 months. Feeding styles had no significant effects on early rapid weight gain and did not interact with formula group. However, type of infant formula had a direct and independent impact on early rapid weight gain ( P  = 0.003). Conclusions: The type of infant formula had a differential impact on early rapid weight gain independent of maternal feeding style, highlighting the self‐regulatory capabilities of infants.